2019
DOI: 10.1111/jfpp.14182
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Asian spices as a mitigation strategy to control heterocyclic aromatic amines in charcoal grilled lamb patties

Abstract: The influence of Asian spices on the heterocyclic aromatic amines (HAAs) in charcoal grilled lamb patties was investigated using the QuEChERSmethod combined with UPLC‐MS/MS. The results showed that ginger, Chinese prickly ash, and cinnamon had strong inhibition in the formation of both nonpolar and polar HAAs (p < .05). The inhibition efficiency of spices for polar HAAs and nonpolar HAAs was in the range of 46%–98% and 31%–99%, respectively. All spices exhibited good scavenging activity for DPPH free radicals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…7 Second, the contents of PhIP, Harman, and Norharman were 20.83, 88.59, and 98.68 ng/g, respectively, in the charcoal roasted lamb at 450−500 °C for 10 min, and their contents reached 73.32, 95.18, and 312.45 ng/g, respectively, when roasted for 14 min. 6 Bordas also reported that the concentration of HAs increased with an increase in the temperature and an extension of the cooking time in a meat model system. 10 pH is known to influence the Maillard reactions and therefore the formation of HAs.…”
Section: ■ Introductionmentioning
confidence: 87%
See 3 more Smart Citations
“…7 Second, the contents of PhIP, Harman, and Norharman were 20.83, 88.59, and 98.68 ng/g, respectively, in the charcoal roasted lamb at 450−500 °C for 10 min, and their contents reached 73.32, 95.18, and 312.45 ng/g, respectively, when roasted for 14 min. 6 Bordas also reported that the concentration of HAs increased with an increase in the temperature and an extension of the cooking time in a meat model system. 10 pH is known to influence the Maillard reactions and therefore the formation of HAs.…”
Section: ■ Introductionmentioning
confidence: 87%
“…The identification and quantification of HAs were conducted following our previous method with a UHPLC–MS/MS (6470, Agilent, USA) equipped with a triple quadrupole. ESI was conducted using a needle voltage of 4 kV; nitrogen was used as the drying agent (10 L/min, 200 °C), the nebulizer gas was 40 V, the flow rate was 11 L/min, and the capillary temperature was 260 °C.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ginger is another most widely used spice either alone or in combination with garlic. For instance, Suleman et al (2019) demonstrated that ginger (0.5-2.5%) possesses the highest efficiency in inhibiting the formation of both polar and nonpolar HAAs (74-99% and 42-100%) in charcoal grilled lamb patties (10-12 min to attain core temperature of 72 • C), followed by cinnamon, Chinese prickly ash, red chili, cumin, and black pepper, with the inhibition efficiency by all the six spices added separately ranging from 46 to 99% for polar HAAs and 31 to 100% for nonpolar HAAs. Similarly, among various spices such as ginger, onion, garlic, red chili, paprika, black pepper, and tomato evaluated for HAAs inhibition efficiency, ginger powder was the most effective in reducing total HAAs content in fried beef and chicken meatballs (180 • C) (Lu, Kuhnle, & Cheng, 2018), while tomato and ginger showed a maximum reduction in MeIQx (77 and 69%), 4,5-DiMeIQx (80 and 71%), and PhIP (79 and 66%) (Khan et al, 2017).…”
Section: Inhibition Of Spice/herbs On Haas Formationmentioning
confidence: 99%